PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP RETURN SAHAM PADA PT BANK BTPN SYARIAH TBK DI INDONESIA - Daulay, Nurfia Sintia (Jaksya: Jurnal Akuntansi Syariah, 2024)
This study aims to determine the effect of Return On Assets, Return On Equity and Debt To Equity Ratio on stock returns at PT Bank BTPN Syariah Tbk in Indonesia. Stock Return is the expected rate of return on investments made in shares or several groups of shares through a portfolio. If Return On Assets increases, stock returns also increase. If Return On Equity decreases, stock returns also decrease and vice versa, if Return On Equity increases, stock returns also increase. If the Debt To Equity Ratio decreases, the stock return will increase. The data used in this research is the company's annual report of PT Bank BTPN Syariah Tbk. The method used in this variable is multiple regression analysis, the results of the study show that the variables ROA, ROE and DER jointly have a significant positive effect on Stock Returns at PT Bank BTPN Syariah Tbk in Indonesia in 2019-2022, while partially ROA and DER on Stock Returns at PT Bank BTPN Syariah Tbk in 2019-2022 and there is an effect of Return On Equity on Stock Returns at PT Bank BTPN Syariah Tbk in 2019-2022.